PEMBELAJARAN PRAKARYA DENGAN MENGGUNAKAN MEDIA KAIN PERCA BAGI SISWA KELAS X MADRASAH ALIYAH DR. IBNU MAS'UD WIRADESA PEKALONGAN - Afnika, Fifi Nur (Universitas Negeri Semarang, 2016)
This research uncover problems: (1) how the structure of art project learning by patchwork medium on student class X Madrasah Aliyah Wiradesa ?, (2) how the work art projects of students grade X Madrasah Aliyah Wiradesa?. This research is using research development method conducted by under control observation. The data collection was done through observation Interviews, and documentation. An analysis of data using reduction of data, presentation of data, and verification. Qualitative analysis with descriptive approach. The research results is,(1) the form of learning the art projects to the patchwork media for class X MA Dr. Ibnu Mas'ud Wiradesa students, designed for the purpose, matter, media, strategy , and evaluation, (2) after learning, obtained the work of the art projects a patchwork class X MA Dr. Ibnu Mas'ud Wiradesa Pekalongan students. The work of students on the aesthetic mostly in good category that btained by seven students or 40,9 % of students. On aspects of conformity calligraphy, most students works included in the category of appropriate obtained by 11 students or 50 % ofstudents. Creativity aspects, most of the work of students included in the good category that obtained by 18 students or 81,81 % of students. Based on the research done can be given advice to the head master to use patchwork as a work medium on learning the art projects for class X MA Dr. Ibnu Mas'ud Wiradesa students.